Językowa obiektywizacja konceptu „wesele” w języku rosyjskim - Ruczina, Ludmiła (Studia Rossica Posnaniensia, 2010)
To form an intercultural competence, one has to learn national concepts that reflect traditions and rites. Wedding rites are among the most important ones in human life. This paper presents the results of cognitive analysis of the concept of wedding made on the basis of Russian folklore, and interviews with contemporaries. The semantic content of the concept of wedding is represented by cognitive characteristics revealed on the basis of the analysis of the meaning, paradigmatic and syntactic relations of the lexeme that nominates the concept, and the associative experiment.